2005
DOI: 10.1007/s11274-004-3318-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial screening and active compound isolation from marine bacterium NJ6-3-1 associated with the sponge Hymeniacidon perleve

Abstract: Twenty-nine marine bacterial strains were isolated from the sponge Hymeniacidon perleve at Nanji island, and antimicrobial screening showed that eight strains inhibited the growth of terrestrial microorganisms. The strain NJ6-3-1 with wide antimicrobial spectrum was identified as Pseudoalteromonas piscicida based on its 16S rRNA sequence analysis. The major antimicrobial metabolite, isolated through bioassay-guide fractionation of TLC bioautography overlay assay, was identified as norharman (a beta-carboline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 32 publications
0
55
0
7
Order By: Relevance
“…The TLC bioautography was determined by agar-overlay method (Zheng et al, 2005). The TLC plate was placed in a sterile Petri plate and 20 ml of molten Mueller Hinton Agar was poured into plate (Hi media, Mumbai, India), aseptically.…”
Section: Tlc Based Bioautography (Agar-overlay Method)mentioning
confidence: 99%
“…The TLC bioautography was determined by agar-overlay method (Zheng et al, 2005). The TLC plate was placed in a sterile Petri plate and 20 ml of molten Mueller Hinton Agar was poured into plate (Hi media, Mumbai, India), aseptically.…”
Section: Tlc Based Bioautography (Agar-overlay Method)mentioning
confidence: 99%
“…Marine sponge-associated microbes rely on sponges for nutrient acquisition and secondary metabolite production (Hentschel et al, 2002). The various secondary metabolites synthesized by microbial associates also possess excellent bioactivity in many studies (Pimentel-Elardo et al, 2010;Liu et al, 2005;Bringmann et al, 2003Bringmann et al, , 2005Zheng et al, 2005). Thus, sponge-associated micro-organisms represent an attractive source of marine natural products.…”
Section: Introductionmentioning
confidence: 99%
“…There is a continuous interest in the -carboline alkaloids representing an important class of synthetic and naturally occurring heterocycles with a wide spectrum of valuable pharmacological properties [1][2][3][4][5][6]. In the recent decades it was also demonstrated that -carboline alkaloids may have a pronounced potential as anti-cancer agents [7][8][9][10][11][12][13][14][15][16], which can act through different mechanisms including eg.…”
Section: Introductionmentioning
confidence: 99%